Tracer Study of Building Engineering Education Graduates for Academic Year 2012-2015 - Ramadhanti, Fitri; E. Nayono, Satoto; Dahar Minghat, Asnul; Rizal, Fahmi (International Journal of Engineering and Technology, 2018)
This study originated from the absence of career data from graduates of the Building Engineering Education Study Program at Padang State University. The purpose of this tracer study is to obtain data on graduate work, specifically the objectives to be achieved are knowing the career choices of graduates of Building Engineering Education study programs. Data collection techniques using a Guttman scale questionnaire and data analysis techniques using descriptive analysis. The population in this study were students graduating from the S-1 Building Engineering Education study program from graduates in 2012 to 2015. The sampling technique used was purposive sampling with a sample of 88 respondents. Data found that 88 graduates who had worked were 96.59% with a description of 30.68% working in the education sector, 52.68% working in construction services and 13.64% working in other fields. The biggest factor influencing career choices in education is the internal factor with sub indicators of work characteristics 88.89%. Factors influencing career choices in construction services are external factors with 93.48% sub indicator of communication and financial awards (salary) 83.33%. Factors that influence career choices in other fields are external factors with sub indicators of the graduate process getting a job 12.50%.